2011
DOI: 10.5732/cjc.011.10226
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-mesenchymal transition in breast cancer progression and metastasis

Abstract: Breast cancer is the most common cancer in women, and approximately 90% of breast cancer deaths are caused by local invasion and distant metastasis of tumor cells. Epithelial-mesenchymal transition (EMT) is a vital process for large-scale cell movement during morphogenesis at the time of embryonic development. Tumor cells usurp this developmental program in order to execute the multi-step process of tumorigenesis and metastasis. Several transcription factors and signals are involved in these events. In this re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
142
1
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 197 publications
(147 citation statements)
references
References 84 publications
2
142
1
2
Order By: Relevance
“…Claudins in general and claudin-4 in particular have a known involvement in epithelial-to-mesenchymal transition (EMT), the complex stepwise phenomenon that occurs during both embryonic development and very-early during tumorigenesis (25). A recent link between EMT and cancer stem cells has sparked considerable interest, because it is widely accepted that only a minor population of tumor cells can initiate and support the development of tumors, and the highly aggressive tumor cells share many characteristics of embryonic progenitor cells.…”
Section: Discussionmentioning
confidence: 99%
“…Claudins in general and claudin-4 in particular have a known involvement in epithelial-to-mesenchymal transition (EMT), the complex stepwise phenomenon that occurs during both embryonic development and very-early during tumorigenesis (25). A recent link between EMT and cancer stem cells has sparked considerable interest, because it is widely accepted that only a minor population of tumor cells can initiate and support the development of tumors, and the highly aggressive tumor cells share many characteristics of embryonic progenitor cells.…”
Section: Discussionmentioning
confidence: 99%
“…These complex sets of events disrupt mainly the tight junctions, desmosomes and promote the transition of epithelial to transient mesenchymal cells via type 3 EMT (Foroni et al, 2012). Motility, invasiveness, and anokis resistance of the metastatic breast cancer cells are derived from oncogenic epithelial to mesenchymal transition (EMT) through the loss of E-cadherin expression with the increase in fibroid morphology (Drasin et al, 2011;Wang and Zhou, 2011;Dave et al, 2012). Cells undergoing EMT, attack the adjacent stroma resulting in the invasion and intravasation of cells in the circulation either individually or as mass.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…An important molecular event is the overexpression of epidermal growth factor receptor (EGFR) and activation of its downstream signaling [4]. Two recent studies have indicated that EGFR was detectable in more than 95% of patients with pancreatic cancer [5,6].…”
Section: Introductionmentioning
confidence: 99%